Born to Trouble - Bradshaw, Rita (UK BCA, 2009)
Born into the worst of families in Sunderland's filthy, crime-ridden East End, Pearl Croft's childhood is miserable. Shortly after her violent, drunken father is killed in a fight, Pearl's elder brothers are sent to prison leaving her, still a child herself, to care for her baby brothers. Pearl's mother brings her "clients" to the house, one of whom has a penchant for little girls ... Terrified and hurt, Pearl runs away from home and is found, feverish and near death, by Romany gypsies. But this is far from the end of Pearl's struggles. Years pass, and as Pearl reaches womanhood she begins to wonder if she is simply born to trouble or will she find happiness one day?
Keywords: Gunfights